A new species of Aristolochia subgenus Siphisia (Aristolochiaceae) from central Vietnam - Do, Truong Van; Neinhuis, Christoph; Wanke, Stefan (Phytotaxa, 2015)
Aristolochia annamensis, a new species from central Vietnam, is described and illustrated. This new species, belonging to Aristolochia subgenus Siphisia, is characterized by a truncate to slightly cordate leaf base, a strongly constricted, a straight, oblong, cylindrically-shaped upper tube without veins, 3–3.2 cm long, limb subcordate with margin of three lobes somewhat recurved, but not revolute, inner surface of limb smooth, annulus absent, throat densely covered with purple dots. In addition to the description, line drawings, ecology, conservation status as well as comparison with morphologically similar species are provided.